High-Concentrate Diets Improve Performance but Challenge Thermoregulation in Sheep - Ribeiro, P. H. C.; de Lima Junior, V.; Menezes, M. dos S.; de Souza Filho, D. F.; de Melo, B. K. C.; Urbano, S. A.; Borba, L. H. F.; Tres, T. T.; Gonçalves, J. de L.; Marques, C. A. T.; Torreão, J. N. da C. (Tropical Animal Science Journal, 2026)
High-concentrate diets improve body performance and alter diet digestion rates, potentially affecting thermoregulation and well-being in sheep. This study aimed to evaluate the effect of increasing concentrate on intake, digestibility of nutrients, ingestive behavior, and physiological parameters in sheep. Twenty-four male Dorper lambs with an initial weight of 16.8 ± 3.5 kg and an age of 60 ± 4.5 days were randomly assigned to diets with increasing levels of concentrate: 45%, 59%, 73%, and 87%. Tifton 85 hay was used as a fiber source. The data were analyzed as a completely randomized design and subjected to orthogonal contrast analysis for linear and quadratic effects for dietary concentrate levels as a fixed effect, at a significance level of p≤0.05. The increase in concentrate increased daily weight gain (0.094 to 0.233 kg/day), dry matter intake, number of meals, and physiological parameters, while reducing neutral detergent fiber intake, digestibility of nutrients, rumination time, and meal duration. The heart rate, respiratory rate, and rectal temperature were positively correlated with concentrate level and negatively correlated with meal duration and total chewing time. Increasing concentrate improves the intake of nutrients and the performance of lambs, but it also increases thermoregulatory rates. Diets with 73% concentrate allow for higher performance with a slight increase in rectal temperature. Physiological parameters are more affected by concentrate levels than by fiber levels.